2017
DOI: 10.1111/cge.13067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel BCL11A variants in patients with epileptic encephalopathy: Expanding the phenotypic spectrum

Abstract: BCL11A encodes a zinc finger protein that is highly expressed in hematopoietic tissues and the brain, and that is known to function as a transcriptional repressor of fetal hemoglobin (HbF). Recently, de novo variants in BCL11A have been reported in individuals with intellectual disability syndrome without epilepsy. In this study, we performed whole-exome sequencing of 302 patients with epileptic encephalopathies (EEs), and identified 2 novel BCL11A variants, c.577delC (p.His193Metfs*3) and c.2351A>C (p.Lys784T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…The findings of the current study confirmed that CDKN2B-AS1 could bind to and regulate the expression of a transcription factor BCL11A, which then can associate with the MAP4K1 promoter so as to inhibit the expression of MAP4K1. BCL11A, encoding an acetylene (Cys2-His2) zinc finger transcription factor, is widely expressed in hematopoietic cells as well as brain and recently emerged as a protein correlated with hematopoietic malignancies (41). BCL11A is up-regulated in several B-cell lymphomas resulting from chromosomal translocations (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the current study confirmed that CDKN2B-AS1 could bind to and regulate the expression of a transcription factor BCL11A, which then can associate with the MAP4K1 promoter so as to inhibit the expression of MAP4K1. BCL11A, encoding an acetylene (Cys2-His2) zinc finger transcription factor, is widely expressed in hematopoietic cells as well as brain and recently emerged as a protein correlated with hematopoietic malignancies (41). BCL11A is up-regulated in several B-cell lymphomas resulting from chromosomal translocations (42).…”
Section: Discussionmentioning
confidence: 99%
“…MAP4K1, also considered to be a hematopoietic progenitor kinase 1 (43), has been demonstrated to participate in hematopoietic cell proliferation and apoptosis (18). Yoshida et al verified the vital roles of MAP4K4 and some lncRNAs in regulating embryo implantation (41). Strikingly, inflammation was reported to be one of the physiopathology processes to evaluate the pathogenesis of cerebral infarction (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports examining patients carrying heterozygous Bcl11 mutations not only revealed severe defects of the immune system but also neurodevelopmental disorders including intellectual disabilities (Dias et al, 2016;Punwani et al, 2016;Lessel et al, 2018;Soblet et al, 2018;Yoshida et al, 2018;Peron et al, 2019). In the case of Bcl11a the mutations analyzed so far reside at the amino terminal end most likely preventing protein-protein interactions, e.g., homodimerization for nuclear localization and complex building of factors required for DNA binding, leading to impaired transcriptional regulation (Dias et al, 2016).…”
Section: Bcl11 Transcription Factors and Neurological Disordersmentioning
confidence: 99%
“…Since its discovery through human genetics, BCL11A, a zinc finger protein expressed in numerous tissues, has been validated as a repressor of HbF expression by knockdown and knockout in primary human erythroblasts, erythroid cell lines and mouse knockout models (Sankaran et al , , ; Bauer & Orkin, ; Canver et al , ). Naturally occurring rare variants, which were discovered in individuals with an autism‐like neurological syndrome (see below), have shown that haploinsufficiency of BCL11A results in derepression to about 15% HbF on average, a level similar to that of HPFH syndromes that protect against co‐inherited β‐haemoglobinopathies (Basak et al , ; Funnell et al , ; Dias et al , ; Yoshida et al , ).…”
Section: Molecular Regulators Of the Switchmentioning
confidence: 99%